A Fully Polynomial-Time Approximation Scheme for Single-Item Stochastic Inventory Control with Discrete Demand - Halman, Nir; Klabjan, Diego; Mostagir, Mohamed; Orlin, Jim; Simchi-Levi, David (Mathematics of operations research, 2009)
The single-item stochastic inventory control problem is to find an inventory replenishment policy in the presence of independent discrete stochastic demands under periodic review and finite time horizon. In this paper, we prove that this problem is intractable and design for it a fully polynomial-time approximation scheme.